2018
DOI: 10.1101/405563
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Body mass index trajectories preceding first report of poor self-rated health: a longitudinal case-control analysis of the English Longitudinal Study of Ageing:

Abstract: Body% mass% index% trajectories% preceding% first% report% of% poor% self5rated% health:% a% longitudinal%case5control%analysis%of%the%English%Longitudinal%Study%of%Ageing% % Adam%Hulman" Word%count%main%text/abstract%2717/246"% Number%of%tables/figures"1/3" References%24" % Keywords%SelfIrated"health,"body"mass"index,"longitudinal"caseIcontrol"study,"trajectory" 2" ! ABSTRACT% Background%Studies"have"consistently"found"that"obesity"is"associated"with"poor"selfIrated" health,"but"how"body"mass"index"(BMI)"deve… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…More than 38.9% of US adults have obesity [1] ; however, much of our understanding of the BMI-mortality association comes from single-time BMI measurement, without considering within-person variation over the long term. Since weight change is highly variable across adulthood, more studies are now focusing on BMI trajectories and different health outcomes [ 11 , 13 , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , 32 ]. However, most of these studies were grouping people using growth curve model or group-based latent model [ 11 , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More than 38.9% of US adults have obesity [1] ; however, much of our understanding of the BMI-mortality association comes from single-time BMI measurement, without considering within-person variation over the long term. Since weight change is highly variable across adulthood, more studies are now focusing on BMI trajectories and different health outcomes [ 11 , 13 , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , 32 ]. However, most of these studies were grouping people using growth curve model or group-based latent model [ 11 , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] ].…”
Section: Discussionmentioning
confidence: 99%
“…Although increasing number of studies have investigated the relationship of BMI trajectories and cardiovascular outcomes, most were assuming the population lies within a mixture of latent groups, using either growth curve model or group-based latent model [ 11 , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] ]. These models are largely based on subgroup means over a specific period of time and might be imprecise.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The associations between underweight and poor SRH strengthened with age, whereas those between the high BMI and poor SRH attenuated with age. Hulman et al reported that the BMI trajectory of those who reported poor SRH had declined more than that of those not reporting poor SRH in subjects aged over 80 years [ 38 ]. Similar to this study, a large population-based cohort study of 3.6 million adults in the UK reported that the associations between BMI and mortality varied by age and those between high BMI and mortality attenuated with age [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, the relationship between underweight and LUTS may reflect reverse causation. Poor QoL leads to weight loss [30], and LUTS deteriorates several indicators of QoL, such as sleep quality, depression, mobility, and self-rated health [31].…”
Section: Discussionmentioning
confidence: 99%